Enhancing Personal Health Record Adoption Through the Community Pharmacy Network: A Service Project - Michael Veronin (University of Minnesota Libraries Publishing, 2015)
Personal Health Records, or PHRs, are designed to be created, maintained and securely managed by patients themselves. PHRs can reduce medical errors and increase quality of care in the health care system through efficiency and improving accessibility of health information. Adoption of PHRs has been disappointingly low. In this paper a project is described-essentially a call for action-whereby the skills, expertise, and accessibility of the community pharmacist is utilized to address the problem of poor PHR adoption. The objective of this proposed project is to promote the expansion of PHR adoption directly at the consumer level by utilizing the existing infrastructure of community pharmacies. The ADDIE model can provide the framework for PHR adoption in community pharmacies. ADDIE is an acronym that stands for the 5 phases contained in the model: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. ADDIE is a versatile educational model used for creating instructional materials, and has found utility as a guidance model for managing projects of all types. By bringing together these concepts: the highly accessible infrastructure of community pharmacies with the educational resources to inform consumers on the proper use of PHRs, the quality of care for patients will be greatly enhanced.   Type: Idea Paper